Is pre-implantation genetic diagnosis (PGD) more of a strain regarding satisfaction with marital quality for male or female partners? A three-year follow-up study. (3rd July 2018) - Järvholm, Stina; Thurin-Kjellberg, Ann; Broberg, Malin
Abstract: Introduction: Men and women with a hereditary genetic disease are faced with different options when they plan to become parents. One is pre-implantation genetic diagnosis (PGD) which is a combination of in vitro fertilization (IVF) and genetic analysis of the embryo before implantation. The present study focuses on how men and women planning for PGD experience the quality of marital satisfaction when they apply for treatment and again, three years later. Methods: The study was a prospective cohort study where all couples ( n  = 22) applying for PGD during 2010 and 2011 were eligible. Nineteen women and 17 men (i.e. 17 couples and two women) participated. Participants answered several questionnaires (Dyadic Adjustment Scale, Hospital Anxiety and Depression Scale and Parental Stress Questionnaire) before PGD treatment, and again three years later. Results: Women who underwent PGD rated the quality of their marital relationship similarly to that of first-time parents and IVF couples, whereas men rated the marital quality somewhat lower than the contrasts groups. Satisfaction with marital quality was stable over the three-year period although men were less satisfied than women on both occasions. At year three, there was a significant correlation between martial satisfaction and parental stress in men, and between martial satisfaction and anxiety and depression in women. Discussion: Men are equally, or more, affected by their situation than their female partners, with consequences for satisfaction with marital quality. For this reason they should be included in any counselling offered.